CD4+T Cell Subset Profiling in Biliary Atresia Reveals ICOS− Regulatory T Cells as a Favorable Prognostic Factor - Zhang, Shuhao; Goswami, Shyamal; Ma, Jiaqiang; Meng, Lu; Wang, Youping; Zhu, Fangming; Zhang, Dandan; Zheng, Shan; Dong, Rui; Xiao, Xianmin; Zhang, Xiaoming; Chen, Gong (Frontiers in Pediatrics, 2019)
Abstract Biliary atresia (BA) is a destructive pediatric liver disease and CD4+T cell activation is demonstrated to play an important role in BA. However, a comprehensive scenario regarding the involvement of CD4+T cell subsets to the development of BA remains unclear. Here, we aim to explore the infiltration of CD4+T cell subsets and their clinical significance in BA. In the present study, thirty BA liver samples were collected during surgery and were divided into good (BA1, n=16) and poor prognosis (BA2, n=14), with samples from choledochal cyst patients (n=8) as control. By using multiplex immunohistochemistry, we evaluated the infiltration level of CD4+T cell subsets in the portal areas. RT-qPCR and flow cytometry were further applied to explore detailed features of Treg subsets. We revealed that hepatic infiltrating Th1, Th2, Th17 and ICOS+Treg cells were significantly increased in BA patients compared to controls and were negatively associated with prognosis, while high infiltrating ICOS-Tregs showed a favourable outcome. Phenotypic analysis indicated that, in contrast to ICOS+Tregs, ICOS-Tregs were mainly CD45RAhiCD45ROlow and preferentially expressed more CD73. Besides, RT-qPCR revealed elevated expression of CD25, CD73, TGF-β and BCL-2 genes in ICOS-Tregs. Finally, functional assay confirmed that ICOS-Tregs had a higher suppressive capacity to cytokine secretion and were more resistant to apoptosis in vitro. Collectively, we demonstrate that a mixed immune response is involved in BA pathogenesis, and the globally enhanced effector CD4+T cell response is associated with unfavourable prognosis, highly suppressive ICOS-Tregs is a protective factor and may serve an important reference to predict prognosis.